Contribution Of Power And Strength Of Arm Muscles To Petanque Shooting Ability In Sport Education Students At Muhammadiyah University Of Surakarta - Chandra Triadi; Nurhidayat (International Journal of Educational Research & Social Sciences, 2021)
This study aims to analyze the contribution of arm muscle power and arm muscle strength to petanque shooting abilities in Sports Education students at Muhammadiyah Surakarta University in 2021. The population and samples used were Students with Interests, Talents, Petanque Sports, Sports Education, Muhaammadiyah University Surakarta, totaling 15 students with sampling technique is purposive sampling. Collecting data using the method of testing and measuring arm muscle power and arm muscle strength and shooting petanque. The analysis used is a correlational study using the help of the SPSS 22.0 application. The results obtained include: First, there is a contribution between arm muscle power and Petanque shooting ability which is obtained Fcount= 4,714 > F_table(1:13) = 4, 670 at = 0.05 and contributed (Ry1) of 0.266 or 26.6%. Second, there is a significant contribution between arm muscle strength and Petanque shooting ability which is obtained by Fcount= 9,552 > F_table (1:13) = 4,670 at = 0.05 and contributes (Ry2) of0.424 or 42.4%. Third, there is a joint contribution between arm muscle power and arm muscle strength to Petanque shooting ability which is obtained Fcount = 4,448 > F_table (2:12) = 3.88 at = 0.05 and contributes (Ry12)0.426. Based on the results obtained, it can be concluded: There is a contribution of arm muscle power to Petanque abilities shooting in UMS sports education students. There is a contribution of arm muscle strength to Petanque shooting ability in UMS sports education students. There is a simultaneous contribution between arm muscle power and arm muscle strength to Petanque shooting ability in UMS sports education students